Eukaryotic yeast V1-ATPase rotary mechanism insights revealed by high-resolution single-molecule studies - Yanagisawa, Seiga; Bukhari, Zain A.; Parra, Karlett J.; Frasch, Wayne D. (Frontiers in Molecular Biosciences, 2024)
Vacuolar ATP-dependent proton pumps (V-ATPases) belong to a super-family of rotary ATPases and ATP synthases. The V1 complex consumes ATP to drive rotation of a central rotor that pumps protons across membranes via the Vo complex. Eukaryotic V-ATPases are regulated by reversible disassembly of subunit C, V1 without C, and VO. ATP hydrolysis is thought to generate an unknown rotary state that initiates regulated disassembly. Dissociated V1 is inhibited by subunit H that traps it in a specific rotational position. Here, we report the first single-molecule studies with high resolution of time and rotational position of Saccharomyces cerevisiae V1-ATPase lacking subunits H and C (V1ΔHC), which resolves previously elusive dwells and angular velocity changes. Rotation occurred in 120° power strokes separated by dwells comparable to catalytic dwells observed in other rotary ATPases. However, unique V1ΔHC rotational features included: 1) faltering power stroke rotation during the first 60°; 2) a dwell often occurring ∼45° after the catalytic dwell, which did not increase in duration at limiting MgATP; 3) a second dwell, ∼2-fold longer occurring 112° that increased in duration and occurrence at limiting MgATP; 4) limiting MgATP-dependent decreases in power stroke angular velocity where dwells were not observed. The results presented here are consistent with MgATP binding to the empty catalytic site at 112° and MgADP released at ∼45°, and provide important new insight concerning the molecular basis for the differences in rotary positions of substrate binding and product release between V-type and F-type ATPases.